Practical application of exclusive and inclusive talent management strategy in companies - Savanevičienė, Asta; Vilčiauskaitė, Birutė (Business, Management and Economics Engineering, 2017)
The article deals with the practical application of exclusive and inclusive talent management strategies in order to form and maintain a competitive human resource potential of the company. The features of both exclusive and inclusive talent management strategies were defined and their practical appication in companies of various Lithuaniam industries was studied. The input from the respondents suggests that major companies prefer the inclusive talent management strategy, rather than exclusive. Summing up all the research results, the following conclusions were formulated: the features characteristic to inclusive talent management strategy dominate in the companies of manufacturing, banking, catering, consulting, trade, energy, transport, and agribusiness industries. In the company of technology industry, features of a mixed (having both exclusive and inclusive) talent management strategy are apparent. The company in the construction-engineering industry has the dominating features of exclusive talent management strategy. Inclusive talent management strategy responds to the principles of human potential development-oriented expression and is an important message for the formulation of further insight into talent management, based on the use of internal potential.